3. ANTI-CANCER EFFECT OF NATURAL KILLER CELLS IN AN IMMUNODEFICIENT MOUSE MODEL BEARING HUMAN LUNG CANCER TUMOR (Vietnam Journal of Community Medicine, 2022)
Objectives: To evaluate the anti-cancer effect of natural killer cells in an immunodeficient mousemodel bearing human lung cancer tumor (H460 lineage).Objects and methods: Natural killer (NK) cells were activated, differentiated, and proliferated in thelaboratory until a concentration of at least 107 cells/ml was reached. Immune-deficient mice (nudemice) 6 - 8 weeks old, number of 24 animals, were injected with 106 H460 lineage human lung cancercells under the skin of the thigh to create human lung cancer in nude mice. When the tumor size wasabout 50 - 70mm3 (after 10 days of transplantation), mice were divided into 4 groups (6 animals/group), the treatment groups were injected with NK cells through the tail vein with a dose of 106cells per 10g, 5x106 cells per 10g and 107 cells per 10g, respectively, once a week, for 3 consecutiveweeks, the control group was injected with 0,9% NaCl containing 5% human albumin.Results: The group of mice with H460 human lung cancer treated with NK cells had a smaller tumorvolume, a longer survival time and a lower death rate than the control group with p>0,05 due to smallsample size.Conclusion: The study suggests that natural killer cells were effective against human lung cancer inan immune-deficient mouse model of xenograft cancer.
Keywords: Tế bào diệt tự nhiên, ung thư phổi, chuột thiếu hụt miễn dịch.